LEITURA: PERCEPÇÃO DA ORGANIZAÇÃO TEXTUAL E A CAPACIDADE DA MEMÓRIA OPERACIONAL - Tomitch, Lêda Maria Braga (Intercâmbio, 2010)
The objective of the present study was to analyse the reading processes of better and weaker readers as they read complete and distorted texts organised in terms of Problem/Solution (Hoey, 1979). Results indicated that better readers were more aware of text structure and used this knowledge to organise the flow of information processing, thus not overwhelming working memory with the storage and processing of text information.